Orbital Pseudotumor: Diagnosis and Management in A Secondary Hospital - Rianti Pratiwi; Indra Setiawan (Majalah Oftalmologi Indonesia, 2021)
Objective: To increase the awareness in diagnosing orbital pseudotumor and its management, especially in a peripheral secondary hospital with limited facilities.Case presentation: A 47 years old woman came with left eye (LE) protrusion, blurred vision, retrobulbar pain, and severe headache at regular intervals. This condition begun 8 months ago, and was diagnosed with orbital cellulitis, however the symptoms persisted until now. Physical examination of the LE showed a decreased in visual acuity, protrusion, chemosis and conjunctiva injection, increased in IOP, limited ocular motility, ipsilateral afferent pupillary defect and optic disc oedema. Plain and contrast CT-Scan showed a hypertrophy of ocular muscles with soft tissue swelling. Patient then diagnosed with idiopathic orbital inflammation and immediately prescribed with high dose steroid for 5 days with observation with glucose level observation for toxicity. Afterwards, she was given an oral corticosteroid and was tapered off for the next few weeks. At two months follow up, there were improvement in protrusion, motility and visual acuity. Conclusion: A complete history taking, physical examination and appropriate additional examination are needed. In hospital or clinical setting with limited facilities, a thorough and comprehensive examination are needed in order to establish the diagnosis and management of orbital pseudotumor.